Design of oversampled generalised discrete Fourier transform filter banks for application to subband‐based blind source separation. Issue 9 (1st December 2013) - Peng, Bo; Liu, Wei; Mandic, Danilo P.
Abstract : A novel design of oversampled generalised discrete Fourier transform filter banks is proposed, with application to subband‐based convolutive blind source separation (BSS), where either instantaneous BSS algorithms or joint BSS algorithms can be applied. Conventional filter banks design is usually focused on elimination of the overall aliasing error and the perfect reconstruction (PR) condition, which are required by traditional subband adaptive filtering applications. However, because of the unknown scaling factor, the traditional PR condition is not necessary in the context of subband BSS and can be relaxed in the design. Owing to the increased degrees of design freedom, the authors can introduce an additional cost function to enhance the mutual information between adjacent subband signals. Together with a reduced subband aliasing level, it leads to an improved subband permutation alignment result for instantaneous BSS and an overall better performance for the joint BSS.